PENYULUHAN TENTANG KONDISI FISIK LINGKUNGAN RUMAH DENGAN PENCEGAHAN PENYAKIT TBC DI DESA PAMENGKANG SERANG BANTEN TAHUN 2023 - Ismarina Ismarina; Nurce Arifiati, Prihayati, Marthia Ikhlasiah (Adiba Aisha Amira, 2023)
Community service activities in the form of counseling are a form of student service to the community through providing empowerment assistance, training, counseling, mentoring and to improve the quality of life. Observations were carried out using interview methods and looking directly into the field. Based on the results of observations and identifying existing problems in Pamengkang Village, Serang, Banten. So one of the work programs was determined, namely